Flame-retardant PC composite material and preparation method thereof

By combining modified nano-silicon balls, carbon balls and silicone balls with polycarbonate and graphite modified polycarbonate, a dense blocking layer and pore structure is solved, and the smoke and performance degradation of polycarbonate materials during combustion is solved. The problem of high-efficiency flame retardant and improved mechanical properties.

CN119242012AActive Publication Date: 2025-01-03JIANGSU LIHAN TECH CO LTD

Patent Information

Application Number
CN202411546557.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-03
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing polycarbonate flame retardant materials produce a large amount of toxic fumes during combustion, and excessive additives lead to a decrease in heat resistance and mechanical properties, making it difficult to meet application needs.

Method used

Modified nano-silicon balls, modified carbon balls and modified silicone balls are used as flame retardants. By combining with polycarbonate and graphite modified polycarbonate, a dense blocking layer and pore structure is formed to improve flame retardant. Performance and mechanical properties.

Benefits of technology

It realizes excellent flame retardant properties, dimensional stability and mechanical properties of polycarbonate composite materials, reduces smoke release, and enhances the overall compatibility and toughness of composite materials, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of flame-retardant materials, in particular to a flame-retardant PC composite material and a preparation method thereof.According to the flame-retardant PC composite material, graphite-modified polycarbonate can improve the flame retardant property of polycarbonate, holes formed when the graphite-modified polycarbonate is heated can play roles in smoke abatement and heat preservation, the overall compatibility is good, dispersion is uniform, and the flame-retardant PC composite material is prepared. In addition, the modified organic silicon balls D, the modified nano silicon balls A and the like are compounded to be used for quenching a combustion chain reaction, isolating oxygen, achieving flame retardance and toughening and reinforcing the polycarbonate base material, and holes in the modified carbon balls C can be used for rapid heat dissipation and prevention of continuous combustion. Meanwhile, oxygen which cannot be isolated by the blocking layer can be diluted, the modified nano silicon spheres B can be used for retarding flame and eliminating smoke, and the defect that the mechanical property of the composite material is reduced due to the formation of holes in a system can be overcome, so that the composite material has relatively high mechanical property while realizing good flame retardance and smoke abatement property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of flame retardant materials, and in particular to a flame retardant PC composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a highly transparent amorphous thermoplastic and one of the five major engineering plastics. It has excellent mechanical properties, electrical properties and oxidation resistance and is widely used in electronics, home appliances, power tools, batteries, charging piles, laptops and other industries and products. Although polycarbonate has certain flame retardancy, its flame retardancy still needs to be further improved in some specific fields.

[0003] At present, the traditional polycarbonate flame retardants mainly include brominated flame retardants, nitrogen-phosphorus flame retardants, sulfonates, etc. Among them, brominated flame retardants are restricted due to the large pollution during use. Therefore, it is necessary to develop new halogen-free flame retardants for polycarbonate. However, due to the addition of a large amount of additives to some existing flame-retardant polycarbonates, although the flame retardancy is improved to a certain extent, the excessive use of additives leads to a decrease in the heat resistance and mechanical properties of the polycarbonate composite materials. In addition, some composite materials will produce a lot of smoke when burning, as shown in the patent technical document CN 116790053B discloses a highly flame-retardant rubber-plastic thermal insulation material and a preparation method thereof. The invention obtains a highly flame-retardant rubber-plastic thermal insulation material by grafting a nitrogen-phosphorus flame retardant into a rubber-plastic thermal insulation material matrix, and blending the obtained modified polyvinyl chloride with a composite functional filler having a core-shell structure with a metal composite material as a shell and nanoclay as a core. Although the rubber-plastic thermal insulation material prepared by this method has high flame retardancy, since the material will produce a large amount of toxic and harmful smoke when heated and burned, the rubber-plastic thermal insulation material provided by this method is still difficult to meet application requirements.

[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a flame retardant PC composite material and a preparation method thereof. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a flame retardant PC composite material and a preparation method thereof, so as to further improve the flame retardancy of the polycarbonate composite material.

[0006] Based on the above purpose, the present invention provides a flame retardant PC composite material and a preparation method thereof.

[0007] A flame retardant PC composite material, comprising the following raw materials by weight: 93.9-106.1 parts of a polycarbonate base material, 6-9.5 parts of a flame retardant, 0.6-1.2 parts of an antioxidant, and 0.4-0.9 parts of a smoke suppressant; The polycarbonate base material is prepared from polycarbonate and graphite-modified polycarbonate; The flame retardant is prepared from modified nano silicon sphere A, modified nano silicon sphere B, modified carbon sphere C and modified organic silicon sphere D; The modified nano-silicon sphere A is nano-silicon dioxide modified by styrene-maleic anhydride copolymer; The modified nano silicon sphere B is a magnesium-doped mesoporous silicon sphere; The modified carbon balls C are prepared from straw, carboxymethyl cellulose and expanded polystyrene balls.

[0008] Preferably, the mass ratio of polycarbonate to graphite-modified polycarbonate in the polycarbonate base material is 76.4-82.5:17.5-23.6; The preparation process of the graphite-modified polycarbonate is as follows: Step A1. Ultrasonic dispersion of expandable graphite in tetrahydrofuran for 25-35 min, and then adding polycarbonate at a rotation speed of 280-300 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; Step A2. Place the mixed solution A in a refrigerator at 0-4°C for 22-24 hours, and then freeze-dry it at -55--50°C and 8-10Pa vacuum conditions for 45-48 hours to obtain graphite-modified polycarbonate; The usage ratio of expandable graphite, tetrahydrofuran and polycarbonate in step A1 is 0.6-0.8 g: 38-42 mL: 2.6-3 g.

[0009] Preferably, the mass ratio of the modified nano-silicon sphere A, the modified nano-silicon sphere B, the modified carbon sphere C and the modified organic silicon sphere D in the flame retardant is 1.7-2.3: 0.8-1.3: 0.5-0.9: 3-4.5.

[0010] Preferably, the preparation process of the modified nano-silicon sphere A is as follows: Step B1. Add silica to an ethanol solution, perform ultrasonic treatment for 8-10 min, and then stir at 70-75° C. and 480-500 rpm for 25-30 min to obtain a mixed solution B1; Step B2. Add ammonia water and KH550 to the mixed solution B1, condense and reflux at 70-75°C for 6-8h, and then centrifuge at a speed of 8000-10000rpm for 8-10min to obtain a mixture B2; Step B3. Add the mixture B2 to DMF, add styrene-maleic anhydride copolymer at a rotation speed of 480-500 rpm, condense and reflux at 86-90°C for 10-12h, and then centrifuge at a rotation speed of 8000-10000 rpm for 8-10min to obtain modified nano-silicon spheres A.

[0011] Preferably, the amount ratio of the silicon dioxide and the ethanol solution in step B1 is 1.5-2 g: 180-200 mL, and the ethanol solution in step B1 is obtained by mixing ethanol and water in a volume ratio of 175:25; In step B2, the ratio of the mixed solution B1, ammonia water and KH550 is 180-200 mL: 4-5 mL: 0.8-1.2 g, and the concentration of the ammonia water is 13%-17%; The usage ratio of the mixture B2, DMF and styrene-maleic anhydride copolymer in step B3 is 1.8-2 g: 145-150 mL: 0.8-1.2 g.

[0012] Preferably, the preparation process of the modified nano-silicon sphere B is as follows: Step C1. Hexadecyltrimethylammonium chloride, triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 hour to obtain a mixed solution A. The mixed solution A was placed at 75-85°C and stirred, and tetraethyl silicate was added dropwise. After reacting for 30 minutes, magnesium chloride solution was added, and stirring was continued for 1 hour to obtain a mixed solution B; Step C2. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 3-5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silicon spheres B; The dosage ratio of the hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl silicate and magnesium chloride solution is 7-8g:1-1.4g:1-1.5mL:1-1.5mL, and the concentration of the magnesium chloride solution is 480-500mg / mL.

[0013] Preferably, the preparation process of the modified carbon ball C is as follows: Step D1. Disperse straw powder, urea and ferric nitrate nonahydrate in deionized water, transfer to a high-pressure reactor and maintain at 160-165° C. for 8-10 hours, centrifuge and vacuum dry to obtain a catalyst; Step D2. The catalyst, carboxymethyl cellulose, expanded polystyrene beads and deionized water are mixed evenly to form beads with a diameter of 2-3 mm. The beads are dried in a vacuum drying oven at 60-65°C for 12-14 hours and then calcined in a tubular furnace at 500-520°C for 2-3 hours to obtain modified carbon balls C.

[0014] Preferably, in step D1, the usage ratio of the straw powder, urea, ferric nitrate nonahydrate and deionized water is 3-5 g: 3-5 g: 1-2 g: 50-55 mL; The straw powder in step D1 is any one of corn straw powder and rice straw powder; The particle size of the urea in step D1 is 1-2 mm; The catalyst, carboxymethyl cellulose, expanded polystyrene beads and deionized water in step D2 are used in a ratio of 1.5-1.8 g: 0.6-0.9 g: 0.05-0.08 g: 2.2-2.6 mL; The particle size of the expanded polystyrene beads in step D2 is 1-2 mm.

[0015] Preferably, the antioxidant is any one of antioxidant HP-136, antioxidant 1010 and antioxidant 168; The smoke suppressant is aluminum hydroxide; The preparation method of the modified organic silicon ball D is as follows: Step E1. Azobisisobutyronitrile, vinyltriethoxysilane and 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide are reacted at 75-80° C. for 8-12 h to obtain intermediate A; Step E2. Mix concentrated hydrochloric acid, methanol and intermediate A evenly, react at 75-80° C. for 22-25 hours, filter and rinse with deionized water to obtain modified organosilicon spheres D; The mass ratio of azobisisobutyronitrile, vinyltriethoxysilane and 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide in step E1 is 0.15-0.18:8-12:10-12; The ratio of concentrated hydrochloric acid, methanol and intermediate A used in step E2 is 2-4 mL: 48-52 mL: 8-12 g; The concentration of the methanol is 99.7%, and the concentration of the concentrated hydrochloric acid is 36.5%.

[0016] A method for preparing a flame retardant PC composite material comprises the following steps: Step S1. mixing polycarbonate and graphite-modified polycarbonate to obtain a polycarbonate base material; Step S2. Mixing the modified nano-silicon ball A, the modified nano-silicon ball B, the modified carbon ball C and the modified organic silicon ball D to obtain a flame retardant; Step S3. The polycarbonate base material, the flame retardant, the antioxidant and the smoke suppressant are mixed evenly, and added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0017] Beneficial effects of the present invention: The invention provides a flame retardant PC composite material and a preparation method thereof. The invention introduces a flame retardant, an antioxidant and a smoke suppressant into a polycarbonate base material, so that the prepared PC composite material has excellent flame retardant performance, dimensional stability and mechanical properties. The polycarbonate and graphite-modified polycarbonate are compounded as the polycarbonate base material, wherein a small amount of graphite-modified polycarbonate is used as a thermal conductive filler to further improve the flame retardant performance of the polycarbonate, and the holes formed when heated can play the role of smoke suppression and heat preservation. In addition, the holes can also be used as carriers of small molecules such as a small amount of modified nano silicon balls B and modified carbon balls C in the flame retardant, and a large amount of modified nano silicon balls A introduced in the flame retardant can make the overall compatibility inside the composite material better and the dispersion uniform, thereby improving the mechanical properties of the composite material to a certain extent.

[0018] The invention provides a flame-retardant PC composite material and a preparation method thereof. The invention uses modified nano-silicon balls A, modified nano-silicon balls B, modified carbon balls C and modified organic silicon balls D as a flame retardant. The modified organic silicon balls D release phosphorus-containing fragments and phenoxy free radicals when the system is heated to quench the combustion chain reaction. Meanwhile, the triethoxysilane structure thereof can also combine with the modified nano-silicon balls A and other components such as a smoke suppressant inside the system to form a cross-linked structure, thereby forming a denser blocking layer, reducing the release of combustible gas and achieving a barrier effect. On the one hand, oxygen can be isolated, and on the other hand, holes in graphite-modified polycarbonate can be sealed to prevent further heat transfer and inhibit further combustion of the composite material. The modified nano-silicon ball A and the modified organic silicon ball D are compounded and enhanced to toughen and strengthen the polycarbonate base material, and the holes contained in the modified carbon ball C in the flame retardant can be used as a heat carrier for rapid heat dissipation to prevent continued combustion, and can also dilute the oxygen that the blocking layer fails to isolate. The metal doped in the modified nano-silicon ball B in the flame retardant can be used for flame retardancy and smoke elimination, and can also make up for the defect of decreased mechanical properties of the composite material caused by the introduction of holes in the modified carbon ball C and graphite-modified polycarbonate, achieving good flame retardancy and smoke elimination while having strong mechanical properties, and thus has broad application prospects. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0020] The sources and properties of some of the raw materials used in the present invention are as follows: The number average molecular weight Mn of the styrene-maleic anhydride copolymer used in the present invention is 28000, and it was purchased from MacLean Chemical Reagent Co., Ltd.; The expandable graphite used in the present invention has a specification of 150 mesh and is purchased from Qingdao Yanhai Carbon Materials Co., Ltd.; The purity of azobisisobutyronitrile used in the present invention is 99.5%, and it was purchased from Beijing Chemical Plant; The 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide used in the present invention was purchased from Eutec Trading (Shanghai) Co., Ltd.; The vinyl triethoxysilane used in the present invention was purchased from Ark Chemical Co., Ltd.

[0021] Embodiment 1: A method for preparing a flame retardant PC composite material, comprising the following steps: S1. 0.6 g of expandable graphite was ultrasonically dispersed in 38 mL of tetrahydrofuran for 25 min, and then 2.6 g of polycarbonate was added at a speed of 280 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; S2. The mixed solution A was placed in a refrigerator at 0°C for 22 hours, and then freeze-dried at -55°C and 8Pa vacuum conditions for 45 hours to obtain graphite-modified polycarbonate; S3. 76.4 g of polycarbonate and 17.5 g of graphite-modified polycarbonate were mixed to obtain a polycarbonate base material; S4. 175 mL of ethanol and 25 mL of water were mixed to obtain an ethanol solution, 1.5 g of silica was added to 180 mL of the ethanol solution, ultrasonically treated for 8 min, and then stirred at 70 ° C and 480 rpm for 25 min to obtain a mixed solution B1; S5. Add 4 mL of 13% ammonia water and 0.8 g of KH550 to 180 mL of mixed solution B1, condense and reflux at 70°C for 6 h, and then centrifuge at 8000 rpm for 8 min to obtain a mixture B2; S6. 1.8 g of the mixture B2 was added to 145 mL of DMF, 0.8 g of styrene-maleic anhydride copolymer was added at a speed of 480 rpm, condensed and refluxed at 86 ° C for 10 h, and then centrifuged at a speed of 8000 rpm for 8 min to obtain modified nano-silicon spheres A; S7. 7 g of hexadecyltrimethylammonium chloride, 1 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 75°C and stirred, and 1 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1 mL of a 480 mg / mL magnesium chloride solution was added, and stirring was continued for 1 h to obtain a mixed solution B; S8. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged three times, the resulting product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silica spheres B; S9. 3 g corn straw powder, 3 g urea with a particle size of 1-2 mm and 1 g ferric nitrate nonahydrate were dispersed in 50 mL of deionized water, and then transferred to a high-pressure reactor and maintained at 160° C. for 8 h, and then centrifuged and vacuum dried to obtain a catalyst; S10. 1.5 g of catalyst, 0.6 g of carboxymethyl cellulose, 0.05 g of expanded polystyrene beads with a particle size of 1-2 mm and 2.2 mL of deionized water were mixed evenly to form beads with a diameter of 2-3 mm, which were dried in a vacuum oven at 60 ° C for 12 h and then calcined in a tubular furnace at 500 ° C for 2 h to obtain modified carbon balls C; S11. 0.15 g of azobisisobutyronitrile, 8 g of vinyltriethoxysilane and 10 g of 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide were reacted at 75° C. for 8 h to obtain intermediate A; S12. 2 mL of 36.5% concentrated hydrochloric acid, 48 mL of 99.7% methanol and 8 g of intermediate A were mixed evenly, reacted at 75° C. for 22 h, filtered and rinsed with deionized water to obtain modified organosilicon spheres D; S13. 1.7 g of modified nano-silicon sphere A, 0.8 g of modified nano-silicon sphere B, 0.5 g of modified carbon sphere C and 3 g of modified silicone sphere D were mixed to obtain a flame retardant; S14. 93.9 g of polycarbonate base material, 6 g of flame retardant, 0.6 g of antioxidant HP-136 and 0.4 g of aluminum hydroxide are mixed evenly, added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0022] Embodiment 2: A method for preparing a flame retardant PC composite material, comprising the following steps: S1. 0.7 g of expandable graphite was ultrasonically dispersed in 39 mL of tetrahydrofuran for 29 min, and then 2.7 g of polycarbonate was added at a speed of 285 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; S2. The mixed solution A was placed in a refrigerator at 1°C for 23 hours, and then freeze-dried at -54°C and 9Pa vacuum conditions for 46 hours to obtain graphite-modified polycarbonate; S3. 79 g of polycarbonate and 19 g of graphite-modified polycarbonate were mixed to obtain a polycarbonate base material; S4. 175 mL of ethanol and 25 mL of water were mixed to obtain an ethanol solution, 1.6 g of silica was added to 185 mL of the ethanol solution, ultrasonically treated for 9 min, and then stirred at 71 ° C and 485 rpm for 26 min to obtain a mixed solution B1; S5. Add 4.2 mL of 14% ammonia water and 0.9 g of KH550 to 185 mL of mixed solution B1, condense and reflux at 71°C for 7 h, and then centrifuge at 8500 rpm for 9 min to obtain a mixture B2; S6. 1.9 g of the mixture B2 was added to 146 mL of DMF, 0.9 g of styrene-maleic anhydride copolymer was added at a speed of 485 rpm, condensed and refluxed at 87 ° C for 11 h, and then centrifuged at a speed of 8500 rpm for 9 min to obtain modified nano-silicon spheres A; S7. 7.4 g of hexadecyltrimethylammonium chloride, 1.2 g of triethanolamine and ultrapure water were mixed and placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 77°C and stirred, and 1.2 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.2 mL of a magnesium chloride solution with a concentration of 485 mg / mL was added, and stirring was continued for 1 h to obtain a mixed solution B; S8. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 4 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silica spheres B; S9. 3.5 g of rice straw powder, 3.5 g of urea with a particle size of 1-2 mm and 1.2 g of ferric nitrate nonahydrate were dispersed in 52 mL of deionized water, and then transferred to a high-pressure reactor and maintained at 162° C. for 9 h, and then centrifuged and vacuum dried to obtain a catalyst; S10. 1.6 g of catalyst, 0.7 g of carboxymethyl cellulose, 0.06 g of expanded polystyrene beads with a particle size of 1-2 mm and 2.3 mL of deionized water were mixed evenly to form beads with a diameter of 2-3 mm, which were dried in a vacuum drying oven at 61 ° C for 13 h and then calcined in a tubular furnace at 505 ° C for 2 h to obtain modified carbon balls C; S11. 0.16 g of azobisisobutyronitrile, 9 g of vinyltriethoxysilane and 11 g of 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide were reacted at 76° C. for 9 h to obtain intermediate A; S12. 3 mL of 36.5% concentrated hydrochloric acid, 49 mL of 99.7% methanol and 9 g of intermediate A were mixed evenly, reacted at 76° C. for 23 h, filtered and rinsed with deionized water to obtain modified organosilicon spheres D; S13. 1.8 g of modified nano-silicon sphere A, 0.9 g of modified nano-silicon sphere B, 0.6 g of modified carbon sphere C and 3.3 g of modified silicone sphere D were mixed to obtain a flame retardant; S14. 95 g of polycarbonate base material, 7 g of flame retardant, 0.8 g of antioxidant 1010 and 0.5 g of aluminum hydroxide were mixed evenly, added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0023] Embodiment 3: A method for preparing a flame retardant PC composite material, comprising the following steps: S1. 0.68 g of expandable graphite was ultrasonically dispersed in 40 mL of tetrahydrofuran for 29 min, and then 2.8 g of polycarbonate was added at a speed of 290 rpm and completely dissolved in tetrahydrofuran to obtain a mixed solution A; S2. The mixed solution A was placed in a refrigerator at 2°C for 24 hours, and then freeze-dried at -53°C and 8-10Pa vacuum conditions for 45-48 hours to obtain graphite-modified polycarbonate; S3. 78 g of polycarbonate and 20 g of graphite-modified polycarbonate were mixed to obtain a polycarbonate base material; S4. 175 mL of ethanol and 25 mL of water were mixed to obtain an ethanol solution, 1.7 g of silica was added to 190 mL of the ethanol solution, ultrasonically treated for 10 min, and then stirred at 72 ° C at a speed of 490 rpm for 27 min to obtain a mixed solution B1; S5. Add 4.4 mL of 15% ammonia water and 1 g of KH550 to 190 mL of mixed solution B1, condense and reflux at 72°C for 8 h, and then centrifuge at 9000 rpm for 10 min to obtain a mixture B2; S6. 2 g of the mixture B2 was added to 147 mL of DMF, 1 g of styrene-maleic anhydride copolymer was added at 490 rpm, condensed and refluxed at 88 ° C for 10 h, and then centrifuged at 9000 rpm for 10 min to obtain modified nano-silicon spheres A; S7. 7.4 g of hexadecyltrimethylammonium chloride, 1.2 g of triethanolamine and ultrapure water were mixed and placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 77 ° C and stirred, and 1.2 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.2 mL of a magnesium chloride solution with a concentration of 490 mg / mL was added, and stirring was continued for 1 h to obtain a mixed solution B; S8. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged three times, the resulting product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silica spheres B; S9. 4 g of rice straw powder, 4 g of urea with a particle size of 1-2 mm and 1.4 g of ferric nitrate nonahydrate were dispersed in 52 mL of deionized water, and then transferred to an autoclave and maintained at 162 ° C for 8 h, and then centrifuged and vacuum dried to obtain a catalyst; S10. 1.7 g of catalyst, 0.8 g of carboxymethyl cellulose, 0.07 g of expanded polystyrene beads with a particle size of 1-2 mm and 2.4 mL of deionized water were mixed evenly to form beads with a diameter of 2-3 mm, which were dried in a vacuum oven at 63 ° C for 12 h and then calcined in a tubular furnace at 510 ° C for 2 h to obtain modified carbon balls C; S11. 0.17 g of azobisisobutyronitrile, 10 g of vinyltriethoxysilane and 12 g of 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide were reacted at 77° C. for 10 h to obtain intermediate A; S12. 4 mL of 36.5% concentrated hydrochloric acid, 50 mL of 99.7% methanol and 10 g of intermediate A were mixed evenly, reacted at 77°C for 22-23-24-25 h, filtered and rinsed with deionized water to obtain modified silicone spheres D; S13. 1.9 g of modified nano-silicon sphere A, 1.1 g of modified nano-silicon sphere B, 0.7 g of modified carbon sphere C and 3.6 g of modified silicone sphere D were mixed to obtain a flame retardant; S14. 100 g of polycarbonate base material, 8 g of flame retardant, 0.8 g of antioxidant HP-136 and 0.6 g of aluminum hydroxide are mixed evenly, added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0024] Embodiment 4: A method for preparing a flame retardant PC composite material, comprising the following steps: S1. 0.7 g of expandable graphite was ultrasonically dispersed in 41 mL of tetrahydrofuran for 34 min, and then 2.9 g of polycarbonate was added at a rotation speed of 295 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; S2. The mixed solution A was placed in a refrigerator at 3°C ​​for 23 hours, and then freeze-dried at -54°C and 9Pa vacuum conditions for 47 hours to obtain graphite-modified polycarbonate; S3. 81g of polycarbonate and 22g of graphite-modified polycarbonate were mixed to obtain a polycarbonate base material; S4. 175 mL of ethanol and 25 mL of water were mixed to obtain an ethanol solution, 1.9 g of silica was added to 195 mL of the ethanol solution, ultrasonically treated for 9 min, and then stirred at 74 ° C and 495 rpm for 29 min to obtain a mixed solution B1; S5. Add 4.5 mL of 16% ammonia water and 1.1 g of KH550 to 195 mL of mixed solution B1, condense and reflux at 74 °C for 7 h, and then centrifuge at 9500 rpm for 9 min to obtain a mixture B2; S6. 1.9 g of the mixture B2 was added to 149 mL of DMF, 1.1 g of styrene-maleic anhydride copolymer was added at a speed of 495 rpm, condensed and refluxed at 89 ° C for 11 h, and then centrifuged at a speed of 9500 rpm for 9 min to obtain modified nano-silicon spheres A; S7. 7.8 g of hexadecyltrimethylammonium chloride, 1.3 g of triethanolamine and ultrapure water were mixed and placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 83 ° C and stirred, and 1.4 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.4 mL of a magnesium chloride solution with a concentration of 495 mg / mL was added, and stirring was continued for 1 h to obtain a mixed solution B; S8. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 3-5 times, the resulting product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silica spheres B; S9. 4.8 g corn straw powder, 4.5 g urea with a particle size of 1-2 mm and 1.8 g ferric nitrate nonahydrate were dispersed in 54 mL of deionized water, and then transferred to a high-pressure reactor and maintained at 164° C. for 9 h, and then centrifuged and vacuum dried to obtain a catalyst; S10. 1.7 g of catalyst, 0.8 g of carboxymethyl cellulose, 0.07 g of expanded polystyrene beads with a particle size of 1-2 mm and 2.5 mL of deionized water were mixed evenly to prepare beads with a diameter of 2-3 mm, which were dried in a vacuum oven at 64 ° C for 13 h and then calcined in a tubular furnace at 518 ° C for 2.5 h to obtain modified carbon balls C; S11. 0.17 g of azobisisobutyronitrile, 11 g of vinyltriethoxysilane and 10.5 g of 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide were reacted at 79° C. for 11 h to obtain intermediate A; S12. 2.5 mL of 36.5% concentrated hydrochloric acid, 51 mL of 99.7% methanol and 11 g of intermediate A were mixed evenly, reacted at 79° C. for 24 h, filtered and rinsed with deionized water to obtain modified organosilicon spheres D; S13. 2 g of modified nano-silicon sphere A, 1.2 g of modified nano-silicon sphere B, 0.8 g of modified carbon sphere C and 4.2 g of modified silicone sphere D were mixed to obtain a flame retardant; S14. 106.1 g of polycarbonate base material, 9 g of flame retardant, 1.1 g of antioxidant 1010 and 0.8 g of aluminum hydroxide were mixed evenly, added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0025] Embodiment 5: A method for preparing a flame retardant PC composite material, comprising the following steps: S1. 0.8 g of expandable graphite was ultrasonically dispersed in 42 mL of tetrahydrofuran for 35 min, and then 3 g of polycarbonate was added at a speed of 300 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; S2. The mixed solution A was placed in a refrigerator at 4°C for 24 hours, and then freeze-dried at -50°C and 10Pa vacuum conditions for 48 hours to obtain graphite-modified polycarbonate; S3. 82.5 g of polycarbonate and 23.6 g of graphite-modified polycarbonate were mixed to obtain a polycarbonate base material; S4. 175 mL of ethanol and 25 mL of water were mixed to obtain an ethanol solution, 2 g of silica was added to 200 mL of the ethanol solution, ultrasonically treated for 10 min, and then stirred at 75 ° C and 500 rpm for 30 min to obtain a mixed solution B1; S5. Add 5 mL of 17% ammonia water and 1.2 g of KH550 to 200 mL of mixed solution B1, condense and reflux at 75°C for 8 h, and then centrifuge at 10,000 rpm for 10 min to obtain a mixture B2; S6. 2 g of the mixture B2 was added to 150 mL of DMF, 1.2 g of styrene-maleic anhydride copolymer was added at a speed of 500 rpm, condensed and refluxed at 90 ° C for 12 h, and then centrifuged at a speed of 10000 rpm for 10 min to obtain modified nano-silicon spheres A; S7. 8 g of hexadecyltrimethylammonium chloride, 1.4 g of triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 h to obtain a mixed solution A. The mixed solution A was placed at 85°C and stirred, and 1.5 mL of tetraethyl silicate was added dropwise. After reacting for 30 min, 1.5 mL of a 500 mg / mL magnesium chloride solution was added, and stirring was continued for 1 h to obtain a mixed solution B; S8. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silica spheres B; S9. 5 g of rice straw powder, 5 g of urea with a particle size of 1-2 mm and 2 g of ferric nitrate nonahydrate were dispersed in 55 mL of deionized water, and then transferred to an autoclave and kept at 165 ° C for 10 h, and then centrifuged and vacuum dried to obtain a catalyst; S10. 1.8 g of catalyst, 0.9 g of carboxymethyl cellulose, 0.08 g of expanded polystyrene beads with a particle size of 2 mm and 2.6 mL of deionized water were mixed evenly to form beads with a diameter of 3 mm, which were dried in a vacuum oven at 65 ° C for 14 h and then calcined in a tubular furnace at 520 ° C for 3 h to obtain modified carbon balls C; S11. 0.18 g of azobisisobutyronitrile, 12 g of vinyltriethoxysilane and 11.5 g of 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide were reacted at 80° C. for 12 h to obtain intermediate A; S12. 3.5 mL of 36.5% concentrated hydrochloric acid, 52 mL of 99.7% methanol and 12 g of intermediate A were mixed evenly, reacted at 80° C. for 25 h, filtered and rinsed with deionized water to obtain modified organosilicon spheres D; S13. 2.3 g of modified nano-silicon sphere A, 1.3 g of modified nano-silicon sphere B, 0.9 g of modified carbon sphere C and 4.5 g of modified silicone sphere D were mixed to obtain a flame retardant; S14. 106.1 g of polycarbonate base material, 9.5 g of flame retardant, 1.2 g of antioxidant 168 and 0.9 g of aluminum hydroxide were mixed evenly, added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

[0026] Comparative Example 1: Compared with Example 1, this comparative example does not add graphite-modified polycarbonate during the preparation of the flame-retardant PC composite material. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a flame-retardant PC composite material is obtained.

[0027] Comparative Example 2: Compared with Example 1, the modified nano-silicon ball A was not added during the preparation of the flame-retardant PC composite material in this comparative example, and the remaining steps and parameters were the same, which will not be repeated in this comparative example, and finally a flame-retardant PC composite material was obtained.

[0028] Comparative Example 3: Compared with Example 1, the modified nano-silicon ball B was not added during the preparation of the flame-retardant PC composite material in this comparative example. The remaining steps and parameters were the same and will not be repeated in this comparative example. Finally, a flame-retardant PC composite material was obtained.

[0029] Comparative Example 4: Compared with Example 1, this comparative example does not add modified carbon balls C during the preparation of the flame-retardant PC composite material. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a flame-retardant PC composite material is obtained.

[0030] Comparative Example 5: Compared with Example 1, this comparative example only adjusts the amount of "polycarbonate" and "graphite modified polycarbonate" in the "polycarbonate base material" from "76.4g" and "17.5g" to "17.5g" and "76.4g", respectively, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a flame-retardant PC composite material is obtained.

[0031] Comparative Example 6: Compared with Example 1, this comparative example only adjusts the amount of "modified nano-silicon ball A" and "modified carbon ball C" in the "flame retardant" from "1.7g" and "0.5g" to "0.5g" and "1.7g", respectively, and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a flame-retardant PC composite material is obtained.

[0032] Performance Testing: Mechanical properties test: The tensile properties were tested in accordance with GB / T1040-1992 on a WDW-50E microcomputer-controlled electronic universal testing machine, with a tensile rate of 200 mm / min, a gauge length of 25 mm, a specimen thickness of 2 mm, and a dumbbell shape. The test results were the average of 5 tests. Limiting Oxygen Index (LOI): The LOI test is carried out on a JF-3 oxygen index tester in accordance with GB / T2406-1993. The standard for measuring the limiting oxygen index of rubber and plastic is that the burning length of the sample is 50mm for 3 minutes, and the sample size is 75mm×13mm×3mm. The test result is the average of 5 tests. Horizontal and vertical burning rating (UL-94): UL-94 vertical combustion grade is carried out on CFZ-3 vertical combustion instrument according to GB / T2408-1980. The grade is divided into V-0, V-1 and V-2 according to the degree of difficulty. The sample size is 125mm×13mm×3mm. The test result is the average value of 5 tests. Smoke Density (SD) and Smoke Density Rating (SDR) Tests: The smoke density (SD) test and smoke density rating (SDR) test were conducted in a JCY-2 building material smoke density box using the national standard GB / T8627-2007. The various sizes of the samples were set to 25mm×25mm×3mm. The test results were the average of three tests. The results are shown in Tables 1 and 2 below: Table 1 Summary of experimental results in Examples 1 to 5 and Comparative Examples 1 to 6

[0033] Data Analysis: It can be seen from Table 1 that the flame-retardant PC composite material prepared by the present invention has higher tensile strength, more excellent flame retardant properties and lower smoke density; This may be because the present invention compounds polycarbonate and graphite-modified polycarbonate as a polycarbonate base material, wherein a small amount of graphite-modified polycarbonate is used as a thermally conductive filler to improve the flame retardant properties of polycarbonate, and the holes formed when heated can play a role in smoke elimination and heat preservation. In addition, the holes can also serve as carriers for a small amount of small molecules such as modified nano-silicon balls B and modified carbon balls C in the flame retardant. Combined with a large amount of modified nano-silicon balls A and modified silicone balls D introduced into the flame retardant, the overall compatibility of the composite material is better and the dispersion is uniform, thereby improving the mechanical properties of the composite material to a certain extent.

[0034] In addition, the present invention uses modified nano-silicon balls A, modified nano-silicon balls B, modified carbon balls C and modified organic silicon balls D as flame retardants. The modified organic silicon balls D release phosphorus-containing fragments and phenoxy free radicals when the system is heated to quench the combustion chain reaction. At the same time, the triethoxysilane structure therein can also combine with the modified nano-silicon balls A and other components such as smoke suppressants to form a cross-linked structure inside the system, thereby forming a denser blocking layer, reducing the release of combustible gases and playing a barrier effect. On the one hand, it isolates oxygen, and at the same time, it can also seal the holes in the graphite-modified polycarbonate to prevent further heat transfer, inhibit further decomposition of the composite material, and achieve flame retardancy and heat preservation. In addition, the modified nano-silicon balls A and the modified organic silicon balls D are compounded and synergistically enhanced to toughen and strengthen the polycarbonate base material, and the flame retardant The holes contained in the modified carbon ball C can be used as a heat carrier for rapid heat dissipation to prevent continued combustion, and can also dilute the oxygen that the blocking layer fails to isolate. The metal doped in the modified nano-silicon ball B in the flame retardant can be used for flame retardancy and smoke elimination, and can also make up for the defect of decreased mechanical properties of the composite material caused by the introduction of holes in the modified carbon ball C and graphite-modified polycarbonate, thereby achieving good flame retardancy and smoke elimination while having strong mechanical properties. In Example 5, when the amount of graphene-modified polycarbonate is increased and the amount of polycarbonate is reduced, the porosity of the composite material increases and the density decreases, so the mechanical properties are significantly reduced. In Example 6, when the amount of modified nano-silicon ball A and modified carbon ball C is changed, the various properties of the composite material also decrease.

[0035] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0036] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A flame retardant PC composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 93.9-106.1 parts of polycarbonate base material, 6-9.5 parts of flame retardant, 0.6-1.2 parts of antioxidant, and 0.4-0.9 parts of smoke suppressant; The polycarbonate base material is prepared from polycarbonate and graphite-modified polycarbonate; The flame retardant is prepared from modified nano silicon sphere A, modified nano silicon sphere B, modified carbon sphere C and modified organic silicon sphere D; The modified nano-silicon sphere A is nano-silicon dioxide modified by styrene-maleic anhydride copolymer; The modified nano silicon sphere B is a magnesium-doped mesoporous silicon sphere; The modified carbon balls C are prepared from straw, carboxymethyl cellulose and expanded polystyrene balls; The modified organic silicon sphere D is a cage-type polysilsesquioxane containing vinyl and phosphorus.

2. The flame retardant PC composite material according to claim 1, characterized in that: The mass ratio of polycarbonate to graphite-modified polycarbonate in the polycarbonate base material is 76.4-82.5:17.5-23.6; The preparation process of the graphite-modified polycarbonate is as follows: Step A1. Ultrasonic dispersion of expandable graphite in tetrahydrofuran for 25-35 min, and then adding polycarbonate at a rotation speed of 280-300 rpm to completely dissolve it in tetrahydrofuran to obtain a mixed solution A; Step A2. Place the mixed solution A in a refrigerator at 0-4°C for 22-24 hours, and then freeze-dry it at -55--50°C and 8-10Pa vacuum conditions for 45-48 hours to obtain graphite-modified polycarbonate; The usage ratio of expandable graphite, tetrahydrofuran and polycarbonate in step A1 is 0.6-0.8 g: 38-42 mL: 2.6-3 g.

3. The flame retardant PC composite material according to claim 1, characterized in that: The mass ratio of the modified nano silicon sphere A, the modified nano silicon sphere B, the modified carbon sphere C and the modified organic silicon sphere D in the flame retardant is 1.7-2.3: 0.8-1.3: 0.5-0.9: 3-4.

5.

4. The flame retardant PC composite material according to claim 1, characterized in that: The preparation process of the modified nano silicon sphere A is as follows: Step B1. Add silica to an ethanol solution, perform ultrasonic treatment for 8-10 min, and then stir at 70-75° C. and 480-500 rpm for 25-30 min to obtain a mixed solution B1; Step B2. Add ammonia water and KH550 to the mixed solution B1, condense and reflux at 70-75°C for 6-8h, and then centrifuge at a speed of 8000-10000rpm for 8-10min to obtain a mixture B2; Step B3. Add the mixture B2 to DMF, add styrene-maleic anhydride copolymer at a rotation speed of 480-500 rpm, condense and reflux at 86-90°C for 10-12h, and then centrifuge at a rotation speed of 8000-10000 rpm for 8-10min to obtain modified nano-silicon spheres A.

5. The flame retardant PC composite material according to claim 4, characterized in that: The amount ratio of silicon dioxide to ethanol solution in step B1 is 1.5-2 g: 180-200 mL, and the ethanol solution in step B1 is obtained by mixing ethanol and water in a volume ratio of 175:25; In step B2, the ratio of the mixed solution B1, ammonia water and KH550 is 180-200 mL: 4-5 mL: 0.8-1.2 g, and the concentration of the ammonia water is 13%-17%; The usage ratio of the mixture B2, DMF and styrene-maleic anhydride copolymer in step B3 is 1.8-2 g: 145-150 mL: 0.8-1.2 g.

6. The flame retardant PC composite material according to claim 1, characterized in that: The preparation process of the modified nano silicon sphere B is as follows: Step C1. Hexadecyltrimethylammonium chloride, triethanolamine and ultrapure water were mixed, placed in a conical flask, and stirred at room temperature for 1 hour to obtain a mixed solution A. The mixed solution A was placed at 75-85°C and stirred, and tetraethyl silicate was added dropwise. After reacting for 30 minutes, magnesium chloride solution was added, and stirring was continued for 1 hour to obtain a mixed solution B; Step C2. After the reaction is completed, the mixed solution B is cooled to room temperature, washed with ethanol and centrifuged 3-5 times, the obtained product is resuspended in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, centrifuged and resuspended again in a sodium chloride-methanol solution and stirred at room temperature for 6 hours, then resuspended with ultrapure water, transferred to a sample bottle and quantified to obtain modified nano-silicon spheres B; The dosage ratio of the hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl silicate and magnesium chloride solution is 7-8g:1-1.4g:1-1.5mL:1-1.5mL, and the concentration of the magnesium chloride solution is 480-500mg / mL.

7. The flame retardant PC composite material according to claim 1, characterized in that: The preparation process of the modified carbon ball C is as follows: Step D1. Disperse straw powder, urea and ferric nitrate nonahydrate in deionized water, transfer to a high-pressure reactor and maintain at 160-165° C. for 8-10 hours, centrifuge and vacuum dry to obtain a catalyst; Step D2. The catalyst, carboxymethyl cellulose, expanded polystyrene beads and deionized water are mixed evenly to form beads with a diameter of 2-3 mm. The beads are dried in a vacuum drying oven at 60-65°C for 12-14 hours and then calcined in a tubular furnace at 500-520°C for 2-3 hours to obtain modified carbon balls C.

8. The flame retardant PC composite material according to claim 7, characterized in that: The usage ratio of the straw powder, urea, ferric nitrate nonahydrate and deionized water in step D1 is 3-5 g: 3-5 g: 1-2 g: 50-55 mL; The straw powder in step D1 is any one of corn straw powder and rice straw powder; The particle size of the urea in step D1 is 1-2 mm; The catalyst, carboxymethyl cellulose, expanded polystyrene beads and deionized water in step D2 are used in a ratio of 1.5-1.8 g: 0.6-0.9 g: 0.05-0.08 g: 2.2-2.6 mL; The particle size of the expanded polystyrene beads in step D2 is 1-2 mm.

9. The flame retardant PC composite material according to claim 1, characterized in that: The antioxidant is any one of antioxidant HP-136, antioxidant 1010 and antioxidant 168; The smoke suppressant is aluminum hydroxide; The preparation method of the modified organic silicon ball D is as follows: Step E1. Azobisisobutyronitrile, vinyltriethoxysilane and 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide are reacted at 75-80° C. for 8-12 h to obtain intermediate A; Step E2. Mix concentrated hydrochloric acid, methanol and intermediate A evenly, react at 75-80°C for 22-25h, filter and rinse with deionized water to obtain modified organosilicon spheres D; The mass ratio of azobisisobutyronitrile, vinyltriethoxysilane and 9,10-dihydro-9-oxo-10-phosphophananthrene-10-oxide in step E1 is 0.15-0.18:8-12:10-12; The ratio of concentrated hydrochloric acid, methanol and intermediate A used in step E2 is 2-4 mL: 48-52 mL: 8-12 g; The concentration of the methanol is 99.7%, and the concentration of the concentrated hydrochloric acid is 36.5%.

10. A method for preparing the flame-retardant PC composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step S1. mixing polycarbonate and graphite-modified polycarbonate to obtain a polycarbonate base material; Step S2. Mixing the modified nano-silicon ball A, the modified nano-silicon ball B, the modified carbon ball C and the modified organic silicon ball D to obtain a flame retardant; Step S3. The polycarbonate base material, the flame retardant, the antioxidant and the smoke suppressant are mixed evenly, and added into a twin-screw extruder for melt blending, extrusion and granulation to obtain a flame-retardant PC composite material.

Citation Information

Patent Citations

  • High-flow environmentally-friendly flame-retardant PC material and preparation method thereof

    CN110272618A

  • Low-smoke high-flame-retardant rubber and plastic thermal insulation material for locomotives and preparation process thereof

    CN119192750A

Cited By

  • Flame-retardant impact-resistant polycarbonate material and preparation method thereof

    CN120988442A